2006
DOI: 10.1002/star.200500455
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Starch from Seeds of Araucaria brasiliensis: A Novel Starch for Application in Food Industry

Abstract: The pinhão seeds (Araucaria angustifolia), are composed of 34% of starch and very low fractions of protein, lipids and phenolic compounds. This composition is favorable to obtain a stable, white in color and odorless starch, useful in the food industry. The isolated starch is constituted predominantly of small‐sized round granules (10–25 μm), rather than oval ones. Compared to corn starch, pinhão starch has a lower temperature and enthalpy of gelatinization. Retrogradation occurs to a lower extent in pinhão st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 30 publications
12
61
2
7
Order By: Relevance
“…Wosiacki and Cereda (1989) reported a similar pattern for pinhão starch at temperatures higher than 85 °C. Bello-Pérez et al (2006) reported an inverse behavior, with higher solubility values for pinhão starch, which according to these authors is in agreement with the lower temperature and enthalpy of gelatinization of pinhão starch assessed by DSC in their study.…”
Section: Paste Freezing and Thaw Stabilitysupporting
confidence: 87%
See 3 more Smart Citations
“…Wosiacki and Cereda (1989) reported a similar pattern for pinhão starch at temperatures higher than 85 °C. Bello-Pérez et al (2006) reported an inverse behavior, with higher solubility values for pinhão starch, which according to these authors is in agreement with the lower temperature and enthalpy of gelatinization of pinhão starch assessed by DSC in their study.…”
Section: Paste Freezing and Thaw Stabilitysupporting
confidence: 87%
“…However, at 70 °C, similarly to a study reported by Stahl et al (2007) and Bello-Pérez et al (2006), the value of the swelling power of pinhão starch was higher compared to that of corn starch. According to these authors, this finding is expected from the known inverse correlation between swelling power and amylose and lipid levels at temperatures close to 85 °C.…”
Section: Swelling Power (Sp) and Solubilitysupporting
confidence: 84%
See 2 more Smart Citations
“…According to the survey on the distribution of Araucaria angustifolia in Brazil by Hueck (1953Hueck ( , 1966, there is no evidence of the natural distribution of this tree in the lowlands of Rio Grande do Sul. It is therefore possible that this occurrence is due to post-Columbian settlers, which would have planted these trees on their lowland farms for wood as well as for the nutrient supply provided by the seeds (Cordenunsi et al 2004;Bello-Perez et al 2006). First settlers from Portugal arrived to the region during the early 19 th century (Corrêa 2013).…”
Section: Introductionmentioning
confidence: 99%